Fine Scale Temporal and Spatial Dynamics of the Stony Coral Tissue Loss Disease Outbreak Within the Lower Florida Keys - Williams, Sara D.; Walter, Cory S.; Muller, Erinn M. (Frontiers in Marine Science, 2021)
One of the latest threats to Florida’s Coral Reef is the stony coral tissue loss disease (SCTLD) outbreak which affects all but a few Caribbean scleractinian species and has spread throughout the Caribbean since 2014. Without a known pathogen, ecological studies of disease dynamics are essential for understanding SCTLD susceptibility at the individual colony and reef level. We investigated the epizootiology of the SCTLD outbreak in the lower Florida Keys at two spatial scales (among reefs ∼1 km and within reefs <10 m) over a 19 month period. In May 2018, three sites absent of SCTLD were established to characterize coral demographics (i.e., live tissue cover and colony diameter) along an offshore to nearshore gradient, and were subsequently surveyed for disease every 2–3 weeks until December 2019. SCTLD was first noted within the offshore and mid-channel reef sites in early October 2018 and later appeared at the nearshore site in early February 2019. SCTLD was negatively correlated with thermal stress, showing reduced progression and incidence rates after 2–3 weeks of water temperatures above the mean monthly maximum temperature for the region (i.e., 2–3 degree heating weeks). Although Pseudodiploria strigosa, Dichocoenia stokesii, Colpophyllia natans, and Diploria labyrinthiformis were the most susceptible species at our sites, areas with more Montastraea cavernosa and Orbicella faveolata colonies had higher prevalence and greater tissue loss associated with disease. The disease was more severe within quadrats with high species diversity, high coral cover, and disproportionately affected larger colonies. Our spatial analyses suggest that (1) SCTLD followed a contagious disease model within small (<10 m) spatial scales, (2) colonies within 1.5–3 m of a diseased coral were at higher risk for subsequently showing disease signs compared with those farther away, and (3) high incidence rates coincided with the loss of small scale (<10 m radius) spatial clustering, suggesting pulses of contagious spread on large spatial scales.